Corporate social responsibility and external stakeholders' health and wellbeing: a viewpoint - Anne-Sofie Hiswåls; Cornelia Wulff Hamrin; Åsa Vidman; Gloria Macassa (SAGE Publishing, 2020)
In recent years there has been increased interest in the role played by business corporate social responsibility (CSR) strategies in promoting the health and wellbeing of internal and external stakeholders. However, the sparse public health research to date has mainly focused on the health and wellbeing of internal stakeholders. This viewpoint article aims to ignite discussion of how CSR strategies need to also target external stakeholders beyond the workplace. Businesses have an opportunity to help address the most important societal challenges, especially the social determinants of health which are the root causes of inequities in health. However, while advancing a new agenda for promoting external stakeholders' health, businesses need to take into account potential challenges that might arise from ethical conflicts when trying to balance their CSR initiatives against their business operations.